A Contingency Analysis of Precarious Organizational Temporariness. (12th August 2016) - Karmowska, Joanna; Child, John; James, Philip
Abstract : This paper extends current understanding of organizational temporariness. The life of a temporary British trade union branch established to recruit Eastern European migrant workers reveals 'precarious temporariness', which is less predictable than the 'planned temporariness' typically portrayed in the literature. This different type of temporariness was associated with four key contingencies affecting the branch: dispersed governance; bottom‐up initiatives; uncertain resourcing; and an effectuation logic. Analysis of the case extends existing understanding of organizational temporariness and points to an extension of existing theorizing by highlighting the contingent nature of temporariness. The broader managerial implication of the findings is that, for projects facing contingencies of the kind studied, the conventional linear approach of target setting and performance management will be less effective than an ongoing process of communication and consultation.